Anti-GD2 IgA kills tumors by neutrophils without antibody-associated pain in the preclinical treatment of high-risk neuroblastoma - Stefan Nierkens; Niels Eijkelkamp; Maaike Nederend; Jeanette Leusen; Mitchell Evers; Marjolein Stip; Kaylee Keller; Hanneke Willemen; Marco Jansen; Chilam Chan; Kevin Budding; Thomas Valerius; et al. (Journal for ImmunoTherapy of Cancer)
Background The addition of monoclonal antibody therapy against GD2 to the treatment of high-risk neuroblastoma led to improved responses in patients. Nevertheless, administration of GD2 antibodies against neuroblastoma is associated with therapy-limiting neuropathic pain. This severe pain is evoked at least partially through complement activation on GD2-expressing sensory neurons.Methods To reduce pain while maintaining antitumor activity, we have reformatted the approved GD2 antibody ch14.18 into the IgA1 isotype. This novel reformatted IgA is unable to activate the complement system but efficiently activates leukocytes through the FcαRI (CD89).Results IgA GD2 did not activate the complement system in vitro nor induced pain in mice. Importantly, neutrophil-mediated killing of neuroblastoma cells is enhanced with IgA in comparison to IgG, resulting in efficient tumoricidal capacity of the antibody in vitro and in vivo.Conclusions Our results indicate that employing IgA GD2 as a novel isotype has two major benefits: it halts antibody-induced excruciating pain and improves neutrophil-mediated lysis of neuroblastoma. Thus, we postulate that patients with high-risk neuroblastoma would strongly benefit from IgA GD2 therapy.